Student workbook for argument-driven inquiry in fourth-grade science : three-dimensional investigations - Sampson, Victor, 1974-; Murphy, Ashley, 1988- (National Science Teachers Association, 2019)
This book provides teachers with student materials for guiding students through argument-driven inquiry investigations. It provides lab details, safety information, and handouts that integrate science, literacy, and math.
Keywords: Science -- Study and teaching (Elementary) -- Activity programs.; Science -- Study and teaching -- Activity programs.; Fourth grade (Education); Sciences -- Étude et enseignement (Primaire) -- Méthodes actives.; Sciences -- Étude et enseignement -- Méthodes actives.; Quatrième année (Éducation); Science -- Study and teaching -- Activity programs; Science -- Study and teaching (Elementary) -- Activity programs